2017
DOI: 10.1007/s00414-017-1544-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of 15 autosomal and 17 Y-STR markers in Sindhi population of Pakistan

Abstract: This study comprises genetic characterization of 15 autosomal and 17 Y-chromosomal STR loci in 103 unrelated male inhabitants of the Sindhi population to establish its lineage and parameters of forensic interest. The examined autosomal STRs revealed high combined power of discrimination, combined power of exclusion, and the combined matching probability as 0.99999999999999999042580, 0.9999977141, and 9.5742 × 10, respectively. A total of 89 unique haplotypes were obtained, of which 84 were observed once with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Significant differences were observed after Boneferroni’s correction ( p ≤ 0.0002) at 15/15 loci with Mongol, 14/15 African American 26 , 27 , Caucasian (12/15) 27 , Uganda Yousafzai and Kashmiri (11/15) 16 , 18 , 28 , Balochi, Punjabi, central India (7/15) 14 , 23 , 38 . While differences at small numbers of loci for Nepalese, Sindhi (3/15), Karnataka and Bangladeshi (2/15) 21 , 24 , 25 , 39 were observed. However, there were no significant differences at any loci for the Tamil, Balmiki, and Kerala populations 19 , 20 , 22 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Significant differences were observed after Boneferroni’s correction ( p ≤ 0.0002) at 15/15 loci with Mongol, 14/15 African American 26 , 27 , Caucasian (12/15) 27 , Uganda Yousafzai and Kashmiri (11/15) 16 , 18 , 28 , Balochi, Punjabi, central India (7/15) 14 , 23 , 38 . While differences at small numbers of loci for Nepalese, Sindhi (3/15), Karnataka and Bangladeshi (2/15) 21 , 24 , 25 , 39 were observed. However, there were no significant differences at any loci for the Tamil, Balmiki, and Kerala populations 19 , 20 , 22 .…”
Section: Resultsmentioning
confidence: 94%
“…We have provided evidence that the Christian population in Lahore, Pakistan, forms a sub-population among Asian groups and has some unique genetic characteristics 14 , 39 , 49 . Results of inter-population differentiations, PCA, phylogenetic and structure analysis revealed that Lahore Christians have relatively close genetic relationships with south Asians particularly Indians.…”
Section: Discussionmentioning
confidence: 98%
“…We compared our current results with previously published work on populations from Pakistan with Yfiler and RM Y-STRs. On Yfiler 17 Y-STRs, British Pakistanis [ 22 ], Punjabi population [ 23 ], Kashmiri population [ 23 ], Hazara population [ 9 ], Sindhi population [ 24 ], Youszai population [ 25 ] and Pathan population [ 26 ] showed discrimination capacities (DCs) of 99.24%, 87.23%, 68.3%, 76.47%, 86.40%, 71.92% and 73.7%, respectively. The samples studied with RM Y-STRs showed HD values ranging from 1 to 0.9921 for Pathan [ 19 ], Brahui [ 19 ], Punjabi [ 19 ], Sindhi [ 19 ], Araein [ 27 ], Pakistani [ 6 ], Punjabi [ 20 ] and Sindhi [ 20 ] populations.…”
Section: Resultsmentioning
confidence: 99%
“…Short tandem repeats show enough variations from individual to individual which make them suitable for personal identification, paternity testing cases, population genetics and evolutionary research (Adnan, Rakha, Oscar, & Kayser, ; Adnan et al, ; Adnan, Ralf, Rakha, Kousouri, & Kayser, ; Adnan, Zhan, Zhan, Kasim, Rakha, & Xin, ; Zhan et al, ). In the present study, we examined the polymorphisms of 15 hypervariable autosomal STR loci in 181 individuals from interior Sindh of Pakistan and compared them with already published data taken from different studies (Barni et al, ; Bentayebi, Abada, Ihzmad, & Amzazi, ; Chen et al, ; Di Cristofaro, Julie, Temori, & Chiaroni, ; Demeter, Kelemen, Székely, & Popescu, ; Perveen, Shahid, Shafique, Shahzad, & Husnain, ; Shafique et al, ; Shan et al, ; Shrivastava, Jain, & Trivedi, ; Tie, Wang, & Oxida, ; Yao & Wang, ; Yoo et al, ; Zhang, , ; Zhang, Zhao, Guo, Liu, & Wang, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%